Effect of Carbon Nanoparticles on the Performance Efficiency of a Solar Water Heater - Al-Salim, Wasan L.; Al-Asadi, Jassim M.; Mahdi, M. A. (Iraqi Journal of Physics, 2022)
Carbon nanoparticles are prepared by sonication using carbon black powder. The surface morphology of carbon black (CB) and carbon nanoparticles (CNPs) is investigated using scanning electron microscopy (SEM). The particles size ranges from 100 nm to 400 nm for CB and from 10 nm to 100 nm for CNPs. CNPs and CB are mixed with silicon glue of different ratios of 0.025, 0.2, 0.05, and 0.1 to synthesis films. The optical properties of the prepared films are investigated through reflectance and absorbance analyses. The ratio of 0.05 for CNPs and CB is the best for solar paint because of its higher solar water heater efficiency and is then added to the silicon glue . Temperature of cold water and temperature of hot water in storage tank were tabulated on hourly basis with the help of an Arduino device. The atmospheric temperature was also noted. It was observed that outlet temperature of water was attained up to 75°C as compared to the inlet water temperature of 23°C for the tank applied with CNP-based paint. The tank applied with CNP-based paint has 4 °C higher water temperature than that coated with CB-based paint after 1 month of test under sun irradiation. Based on the results, the efficiency of a solar water heater depends on the difference in temperature of inlet water and outlet of heater. The efficiency of the solar water heater coated with CNPs is around 77% but the solar water heater coated with CB has an efficiency of  67%.